Sensor Systems and Software Second International ICST Conference, S-Cube 2010, Miami, FL, USA, December 13-15, 2010, Revised Selected Papers - Par, Gerard; Morrow, Philip (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on Sensor Systems and Software, S-Cube 2010, held in Miami, Florida, USA, in December 2010. The 17 revised full papers presented were carefully reviewed and selected and cover a wide range of topics including sensor application programming paradigms, novel sensor applications, sensor network middleware, trust security and privacy, wireless sensor network management and monitoring, and sensor application development support systems.